Climatic Cycles and Gradients of the El Niño Core Region in North Peru. (15th April 2015) - Rollenbeck, Rütger; Bayer, Fabian; Münchow, Jannes; Richter, Michael; Rodriguez, Rodolfo; Atarama, Nestor
Abstract : Climatic processes in northern Peru are evaluated on surface observation independent of modelling studies. The region is characterized by regular oscillations, but episodic El Niño-events introduce strong disturbances. Conceptual models based on observations, remote sensing data, and output of regional climate models are compared with data from a new station network. The results show regular oscillations of all climate variables on the annual and daily time scale. The daily cycle is probably associated with thermotidal forcings, causing gravity waves to emanate from the Andes Cordillera. Main factors are the interaction of large scale pressure systems like the Southeast Pacific High and the intertropical convergence zone (ITCZ). Also, there are regional factors: an extended sea-breeze system, the barrier-effect of the Andes, additional energy input by elevated radiation absorption at the mountain slopes, local wind systems, and the variations of the sea surface temperature. At the coast, a low-level jet works as a thermodynamic energy sink, suppressing deep convection and supporting the aridity. Those patterns are found in most of the station data and the processes of this climate can generally be confirmed. The overturning of this stable system with the onset of El Niño-conditions is possibly caused by disruptions of the regional circulation.